Metode Guru PAK dalam Meningkatkan Kemampuan Berpikir Kritis Siswa di Tinggkat SMP - Indriana Hutagalung; Ordekoria Saaragih (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2025)
This research aims to analyze the learning methods used by Christian Religious Education (PAK) teachers in improving students' critical thinking skills at the junior high school level. The focus of this research is on the use of learning methods such as lectures, discussions, Problem-Based Learning (PBL), and cooperative learning. The approach used is qualitative by collecting data through journals, literature reviews, document studies and e-books. The research location was carried out in North Sumatra Province and its surroundings, Indonesia. The research results show that PAK teachers still predominantly use lecture methods which are less effective in encouraging students to think critically. However, some students have shown potential for critical thinking when given more innovative learning methods, such as PBL and group discussions. Learning methods that actively involve students, such as discussions and cooperative learning, have been proven to be able to increase student participation and develop analytical skills, problem solving and creativity.